Amalgam tattoo: a cause of sinusitis? - José Luiz Santos Parizi; Gisele Alborghetti Nai (University of São Paulo, 2010)
Little attention has been paid to the toxicity of silver amalgam fillings, which have been used over the centuries in Dentistry. Amalgam particles may accidentally and/or traumatically be embedded into the submucosal tissue during placement of a restoration and perpetuate in such area. This article presents a case of amalgam tattoo and investigates whether it is related to the patient's repeated episodes of sinusitis. The patient was a 46-year-old woman with a 2 mm diameter radiopaque lesion in the right oral mucosa detected on a panoramic radiograph and presented as a black macula clinically. A complete surgical resection was carried out. The histopathological examination revealed deposits of dark-brownish pigments lining the submucosal tissue with adjacent lymphocytic inflammatory infiltrate and multinucleated giant cells phagocyting pigments. There was a negative staining for both iron and melanin. One year after lesion removal, the patient reported that the sinusitis crises had ceased after repeated episodes for years. It may be speculated that the inflammatory process related to amalgam tattoo seems to lead to a local immune response that causes sinusitis because it enhances the human leukocyte antigen DR (HLA-DR) tissue expression.